Search for direct pair production of sleptons and charginos decaying to two leptons and neutralinos with mass splittings near the W-boson mass in √s=13 TeV pp collisions with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (Journal of high energy physics, 2023)
A search for the electroweak production of pairs of charged sleptons or charginos decaying into two-lepton final states with missing transverse momentum is presented. Two simplified models of R-parity-conserving supersymmetry are considered: direct pair-production of sleptons l̄ l̄ with each decaying into a charged lepton and a (x) over tilde (+/-)(0)(1)neutralino, and direct pair-production of the lightest charginos ( (x) over tilde (+/-)(1) (x) over tilde (-/+)(1)), with each decaying into a W-boson and a (x) over tilde (0)(1). The lightest neutralino ( (x) over tilde (0)(1)) is assumed to be the lightest supersymmetric particle (LSP). The analyses target the experimentally challenging mass regions where m( (l) over tilde)- m( (x) over tilde (0)(1)) and m( (x) over tilde (+/-)(1))- m((x) over tilde (0)(1)) are close to the W-boson mass (‘moderately compressed’ regions). The search uses 139 fb−1 of √s = 13 TeV proton-proton collisions recorded by the ATLAS detector at the Large Hadron Collider. No significant excesses over the expected background are observed. Exclusion limits on the simplified models under study are reported in the ((l) over tilde , (x) over tilde (0)(1)) and ( (x) over tilde (+/-) (1), (x) over tilde (0)(1)) mass planes at 95% confidence level (CL). Sleptons with masses up to 150 GeV are excluded at 95% CL for the case of a mass-splitting between sleptons and the LSP of 50 GeV. Chargino masses up to 140 GeV are excluded at 95% CL for the case of a mass-splitting between the chargino and the LSP down to about 100 GeV.
Gesehen am 24.04.2024